Flexural behaviour of steel and macro-PP fibre reinforced concretes based on alkali-activated binders. (30th June 2019) - Koenig, Andreas; Wuestemann, Annemarie; Gatti, Federico; Rossi, Laura; Fuchs, Florian; Fessel, Dustin; Dathe, Felix; Dehn, Frank; Minelli, Fausto
Highlights: A slight decrease of the compressive strength and a higher porosity could be observed with fibers. Only StF in Geopolymer- and PPF in AAS-concretes increased the flexural tensile strength. StF reinforced OPC- and AAFA-concretes showed a post-softening behavior. Imperfections on the fiber surface were visualized by µXCT. A post-hardening behavior was determined in all concretes with PPF. Abstract: In the following study, the mechanical properties of steel and macro-PP fibre reinforced concretes based on an alkali-activated slag (AAS), an alkali-activated fly ash (AAFA) and an Ordinary Portland Cement (OPC) were studied. The influence of different fibre materials (macro-PP fibres and steel fibres mix) and contents (0, 0.3 and 0.6 vol%) on the compressive, splitting tensile and flexural tensile strength was investigated at an age of 28 days. The obtained load-deformation curves and the characteristic post crack behaviour (according to EN 14651) were interpreted by additional analyses of the bond behaviour via micro X-ray computer tomography (μXCT) and scanning electron microscopy (SEM).